Brand Love Mediates the Influence of Brand Experience and Brand Trust on Brand Loyalty - Dimas Putra Ardana; I Nyoman Rasmen Adi (Green Publisher Indonesia, 2026)
Uniqlo is a Japanese fashion brand that has garnered a large following in Indonesia due to its simple designs, high quality, and affordable prices. However, in an increasingly competitive business environment, Uniqlo needs to maintain consumer brand loyalty to remain a market leader. This study aims to examine the role of brand love in mediating the influence of brand experience and brand trust on brand loyalty to Uniqlo products. The population used in this study was all Uniqlo fashion customers living in Bali Province, with an unknown exact number. An infinite population is a population whose number cannot be determined with certainty. The sample size in this study was 21 x 5, representing 105 Uniqlo consumers in Bali Province. Data analysis techniques used Structural Equation Modeling (SEM) and Partial Least Squares (PLS) version 4 software for inferential statistical analysis. The results of the study show that brand experience has a significant positive effect on brand love. Brand trust has no effect on brand love. Brand experience has a significant positive effect on brand loyalty. Brand trust has no effect on brand loyalty. Brand love has a significant positive effect on brand loyalty. Brand love is able to mediate the effect of the brand experience system on customer loyalty of the Uniqlo fashion brand in Bali. Brand love cannot mediate the effect of brand trust on brand loyalty of the Uniqlo fashion brand in Bali.